2020
DOI: 10.1038/s41598-020-61315-5
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic characterization of novel H1 influenza A viruses in swine

Abstract: Novel H1N2 influenza A viruses (IAVs) in swine have been identified in Chile co-circulating with pandemic H1N1 2009-like (A(H1N1)pdm09-like) viruses. The objective of this study was to characterize antigenically the swine H1 IAVs circulating in Chile. Genetic analysis based on the HA1 domain and antigenic analysis by hemagglutination inhibition assay were carried out. Three antigenic clusters were identified, named Chilean H1 A (ChH1A), Chilean H1 B (ChH1B), and A(H1N1)pdm09-like. The antigenic sites of ChH1A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…The S183P amino acid change located near the receptorbinding site was a key marker of change for many human influenza A(H1N1)pdm09 viruses that was noticed early in the development of the 2009-2010 pandemic before spreading globally (WHO Influenza Centre London, 2011). D168N amino acid substitution, located at the Ca antigenic site, has also been observed in human and swine influenza A viruses multiple times (Tapia et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The S183P amino acid change located near the receptorbinding site was a key marker of change for many human influenza A(H1N1)pdm09 viruses that was noticed early in the development of the 2009-2010 pandemic before spreading globally (WHO Influenza Centre London, 2011). D168N amino acid substitution, located at the Ca antigenic site, has also been observed in human and swine influenza A viruses multiple times (Tapia et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…Detailed HA sequence analysis of these strains showed that all of them feature D168N amino acid substitutions located at the Ca antigenic site, along with S183P. This explains their poor recognition by antisera raised against the A/California/07/2009 strain and other antigenically related strains (Tapia et al, 2020).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…We had previously reported the identification of the H1N2 strains from Chile, however; the in depth characterization of the ChH1N2B and ChH1N2A clusters presented here (also classified as humans seasonal lineage 1B.2 according to the new proposed designation (Anderson et al, 2016)) had not been done (Nelson et al, 2015a;Tapia et al, 2018;Tapia et al, 2020). The ChH1A virus appears to have spread more efficiently in pigs, since it was found in 12 farms that were geographically unrelated, while ChH1B was only found in two farms (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…However, we did not differentiate between some previously described antigenic clusters 24 , because there are only a few amino acid substitutions in HA1 domain between strains from these clusters. Only amino acid substitution in HA1 domain can cause a high antigenic impact 25 .…”
Section: Discussionmentioning
confidence: 99%